The Multifaceted Impact of Music on Learning in Traditional and Music Schools - SIMION, Anca (Studia Universitatis Babes-Bolyai Musica, 2024)
This paper attempts to delve more into the complex role that music education plays in both traditional and music schools. Beyond teaching skills, music education frames children’s personality and helps them fit in future working environments. Nurturing environments, modelled after music schools, emphasize comprehensive development, integrating cognitive, psychomotor, socioemotional, and artistic aspects. Beyond conventional lines, a holistic approach to education fosters creativity, emotional intelligence, and cross-cultural understanding. Music emphasizes the importance of self-expression and encourages individuals to explore their own unique voice. It also promotes collaboration and teamwork, as musicians often work together to create harmonious melodies. Additionally, music education has been shown to improve cognitive abilities such as problem-solving and critical thinking skills, which can be applied to various areas of life beyond the realm of music. Music schools emphasize immediacy and subjectivity, whereas traditional schools emphasize different feedback mechanisms. Aligning these components have the potential of enhancing learning opportunities and encourage a more comprehensive approach to learning and evaluation in the traditional school setting.